2021
DOI: 10.3390/ma14143935
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Interface and Repairability of 3D-Printed Intraoral Splints: Shear Bond Strength to Current Polymers, with and without Ageing

Abstract: This in-vitro study investigates the bonding interfaces reached by the conditioning of a splint material additively manufactured by digital light processing (AM base) as well as the shear bond strength (SBS) of resins bonded to these surfaces (repair material). Therefore, the AM base was either stored in dry for 12 h or wet environment for 14 days to simulate ageing by intraoral wear. The dry and wet group was bonded after physical and/or chemical conditioning to cylinders made from polymethylmethacrylate or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
3
4
0
Order By: Relevance
“…According to the current study, 3D denture groups, independent of surface treatment, had the greatest mean value in Flexural strength compared to other methyl methacrylate groups. This difference could be attributed to (1) the viscosity of the 3D denture resins or (2) the layered structure of the 3D printed resin, as well as the association and similarity between the original specimen material and repaired material, resulting in a strong chemical bond even without any surface treatment, which is consistent with data obtained in previous studies (19,22) .…”
Section: Discussionsupporting
confidence: 88%
“…According to the current study, 3D denture groups, independent of surface treatment, had the greatest mean value in Flexural strength compared to other methyl methacrylate groups. This difference could be attributed to (1) the viscosity of the 3D denture resins or (2) the layered structure of the 3D printed resin, as well as the association and similarity between the original specimen material and repaired material, resulting in a strong chemical bond even without any surface treatment, which is consistent with data obtained in previous studies (19,22) .…”
Section: Discussionsupporting
confidence: 88%
“…The main limitation of this research is the inability to fully mimic an oral environment by, for example, exposing the materials to multiple environments and multidirectional forces instead of one directed force, as done in this research. Light curing of composites in jigs may have infleunced the bonding, as the composites would receive a direct light source in real life opposed to losing it through the experimental specimen fabrication jig, as reported by a previous study [34]. Therefore, further studies addressing these limitations may be beneficial for more comprehensive and precise results.…”
Section: Discussionmentioning
confidence: 97%
“…Studies done on splints created via AM have shown that conditioners containing methyl methacrylate (MMA) play a vital role in the durability of bond strengths [ 13 ]. Convincing results were also achieved with MMA in the bonding of CAD/CAM composite resin blocks [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various air-abrasion powders with different mean sizes and pressures are described in literature [ 10 – 12 ]. Alumina powder displayed especially promising results [ 13 ] but has been criticized for damaging the surface, whereas air-abrasion with glass pearls would be sufficient [ 14 ]. Only a few in vitro studies have been concerned with the influence of air-particle abrasion on the surface properties of 3D printable resin restorations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%